Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae) - Fernandez-Triana, Jose L (Pensoft Publishers, 2014)
Abstract. This paper is the first to consider braconid parasitoid wasps in conservation efforts in Canada. Out of the 28 genera of the subfamily Microgastrinae (Hymenoptera: Braconidae) present in the country, 13 genera were studied and 16 species were identified as potential candidates to be included in the Species Candidate Lists of COSEWIC (The Committee on the Status of Endangered Wildlife in Canada). For every selected species a brief summary of its broad geographical distribution is provided, with detailed and in many cases new information of its distribution and collecting dates in Canada, hosts (Lepidoptera) if known, and color pictures of all wasp species. A preliminary assessment is made using Prioritization Criteria developed by COSEWIC, and some general recommendations are made based in those analyses.